Características químicas e compostos bioativos de pólen (saburá) de abelhas Scaptotrigona spp - Perusso, Edilaine (2022)
The pollen collected by the stingless bees from the plants is deposited in the colony in exclusive pots, which makes its exploration easy. In these pots, the deposition of some enzymes that help the natural conservation of pollen occurs. Because it is different from pollen in natura, the product of native bees receives special names: saburá or samburá, depending on the region. Since it is a proteinrich compound, it has been increasingly sought after in the natural food market. Therefore, the initiative of beekeepers to explore pollen beyond the honey of these bees is growing. The objective of this research was to characterize the physicochemical composition and bioactive compounds of saburá samples produced by native bees Scaptotrigona sp. The analyzes were carried out in March 2021, with three replications. The average results of the physicochemical compositional analyses, obtained for the collected samples, indicated average percentages of 22.56% for protein contents, 21.15% for lipids and 13.68% for moisture. In the evaluation of the bioactive compounds it was obtained for total flavonoids (760 mg EQ/g), total phenolic compounds (1,840 mg EAG/g) and determination of the antioxidant potential (2,139.66 TEAC µM/g). Studies on this material are necessary to have a quality control, for a better standardization of the pollen of stingless bees for possible uses in the food and pharmaceutical industries, as well as the valorization of products of national origin. This is in view of the growing trade in the product.